2020
DOI: 10.1155/2020/4832010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Influence of Topological Defects on a Relativistic Scalar Particle with Cornell-Type Potential in Cosmic String Space-Time with a Spacelike Dislocation

Abstract: We study the relativistic quantum of scalar particles in the cosmic string space-time with a screw dislocation (torsion) subject to a uniform magnetic field including the magnetic quantum flux in the presence of potential. We solve the Klein-Gordon equation with a Cornell-type scalar potential in the considered framework and obtain the energy eigenvalues and eigenfunctions and analyze a relativistic analogue of the Aharonov-Bohm effect for bound states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…From an extension of Volterra process to 3+1 dimensions, Puntingam and Soleng showed that there was only 10 ways to modify a Minkowski spacetime into different pseudo-Riemann-Cartan geometries with respect to the Poincaré group. For example, a cosmic linear defect can display chirality [114][115][116][117][118][119]: in that case, the defect carries torsion along its axis and one gets the cosmic counterpart of a screw dislocation in a smectic liquid crystal. Twisted Nambu-Goto strings (or cosmic dispirations), consisting in spacetimes with delta function-valued curvature and torsion distributions have also been considered, as they combine both rotational and translational anholonomy [120][121][122][123]: as mentioned earlier, their effects on light could be tested from experiments done with elastic dispirations SmC A and SmC 2 .…”
Section: B Beyond Cosmic Wedge Disclinationsmentioning
confidence: 99%
“…From an extension of Volterra process to 3+1 dimensions, Puntingam and Soleng showed that there was only 10 ways to modify a Minkowski spacetime into different pseudo-Riemann-Cartan geometries with respect to the Poincaré group. For example, a cosmic linear defect can display chirality [114][115][116][117][118][119]: in that case, the defect carries torsion along its axis and one gets the cosmic counterpart of a screw dislocation in a smectic liquid crystal. Twisted Nambu-Goto strings (or cosmic dispirations), consisting in spacetimes with delta function-valued curvature and torsion distributions have also been considered, as they combine both rotational and translational anholonomy [120][121][122][123]: as mentioned earlier, their effects on light could be tested from experiments done with elastic dispirations SmC A and SmC 2 .…”
Section: B Beyond Cosmic Wedge Disclinationsmentioning
confidence: 99%
“…This fascinating approach has been taken on in many subsequent papers. As examples, let us refer to studies on the structure of the curvature tensor of cosmic strings determined by a conical singularity in space-time [32], the behavior of a Klein-Gordon particle in a class of space-times generated by defects [33][34][35][36], in Kaluza-Klein theories [37,38], on the behaviour of a spin-zero Duffin-Kemmer-Petiau's particle in a cosmic string space-time [39] and in a global monopole space-time [40], on the spin and pseudospin symmetries of Dirac particles in topological defect backgrounds [41,42], on the interaction of a scalar field with a Coulomb-type potential in a space-time with a screw dislocation [43], and on non-relativistic quantum dynamics of a single particle interacting harmonically with conical singularities associated with either a cosmic string, a global monopole, a magnetic flux string, or a screw dislocation [44].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, with a clear approach, we can say, the cosmic strings are not only interested in cosmology and field theory but also interested in solids in the context of the linear topological defects. These linear topological defects, in a solid, can be characterized as distortions, which are classified as twist and wedge disclinations, and spiral and screw dislocations [12][13][14]. It is worth mentioning that in this paper we focus only on the spiral dislocation.…”
Section: Introductionmentioning
confidence: 99%